Hypothalamic leptin action is mediated by histone deacetylase 5 - Dhiraj G. Kabra (Nature Portfolio, 2016)
Histone deacetylases (HDACs) regulate energy metabolism in peripheral tissues, but whether HDACs expressed in the brain influence systemic metabolism is unknown. Here the authors show that hypothalamic HDAC5 expression is affected by the diet and HDAC5 regulates leptin sensitivity by deacetylating STAT3.